If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + -79 = 83 Reorder the terms: -79 + h = 83 Solving -79 + h = 83 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '79' to each side of the equation. -79 + 79 + h = 83 + 79 Combine like terms: -79 + 79 = 0 0 + h = 83 + 79 h = 83 + 79 Combine like terms: 83 + 79 = 162 h = 162 Simplifying h = 162
| 3w2w+6= | | (3x+5)-(9x-4)= | | p-0.20p=5 | | 2(1a+2a)= | | (8x+7)-(9x-8)= | | 21=3t | | 3ax-2=5ax-1 | | -3d+5+d15= | | f(x)=6xln(2x)-6x | | 11=-5g-2 | | (3x-1)(10x-3)=0 | | 3x+3(6x-12)=132 | | 3r-4rs+2s= | | 0.07=56 | | 72=9g | | 2X-21+3X-34=180 | | -4(5x+2)+3(x-3)= | | 2w-3(3w+5)=3w+5 | | -8x-5y=15 | | 35-19=3(x-3) | | ?(2x-4)+5=-?(x+1) | | 3x^3+13x^2-16=0 | | 48x^2-16x-20=0 | | -138-6(6b-7)= | | 2n-1=-11 | | 4x+8y=52 | | 3n-8=-20 | | 4x-10=12+4(x+8) | | 2-c=29 | | ?(2x-4)=-?(x+1) | | 4t-1=5(t+5) | | 3x=7x+20 |